Oryza glumaepatula: A wild relative to improve drought tolerance in cultivated rice - Prakash, Parthiban Thathapalli; Chebotarov, Dymetro; Zhang, Jianwei; Kudrna, David A.; Torres, Rolando O.; Natividad, Mignon A.; Quintana, Marinell R.; Song, Jiaming; Maldonado L, Carlos E.; Hechanova, Sherry Lou; Jena, Kshirod; Wing, Rod A.; et al. (Oxford University Press, 2023)
Developing drought-resistant rice (Oryza sativa, L.) is essential for improving field productivity, especially in rain-fed areas affected by climate change. Wild relatives of rice are potential sources for drought-resistant traits. Therefore, we compared root growth and drought response among 22 wild Oryza species, from which Oryza glumaepatula was selected as a promising source for further exploration. A geographically diverse panel of 69 O. glumaepatula accessions was then screened for drought stressrelated traits, and 6 of these accessions showed lower shoot dry weight (SDW) reduction, greater percentage of deep roots, and lower stomatal density (STO) under drought than the drought tolerant O. sativa variety, Sahbhagi dhan. Based on whole-genome resequencing of all 69 O. glumaepatula accessions and variant calling to a high-quality O. glumaepatula reference genome, we detected multiple genomic loci colocating for SDW, root dry weight at 30 to 45 cm depth, and STO in consecutive drought trials. Geo-referencing indicated that the potential drought donors originated in flood-prone locations, corroborating previous hypotheses about the coexistence of flood and drought tolerance within individual Oryza genomes. These findings present potential donor accessions, traits, and genomic loci from an AA genome wild relative of rice that, together with the recently developed reference genome, may be useful for further introgression of drought tolerance into the O. sativa backgrounds.